2002
DOI: 10.1002/1615-9861(200204)2:4<394::aid-prot394>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Proteoglycan and proteome profiling of central human pulmonary fibrotic tissue utilizing miniaturized sample preparation: A feasibility study

Abstract: The objective of this study was to isolate fibrotic cells from human lung biopsies taken from different central pulmonary locations. A comparison was made of cell morphology, proteoglycan- and protein-expression in mesenchymal cell cultures obtained from human bronchial biopsies from patients with asthmatic-like disorders. We isolated viable cells from 10 out of the 12 biopsies. The fibroblast-like cells were positive for the biomarker a-smooth muscle actin, indicating that the cells were in an activated state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 26 publications
(44 reference statements)
0
35
0
Order By: Relevance
“…Cells isolated from diseased lungs also exhibit altered versican production. For example, bronchial fibroblasts cultured from human asthma patients exhibited elevated versican production (20,21). Furthermore, in a study of induced sputum from patients with severe asthma, we found elevated levels of versican and HA over a 16-week period, which inversely correlated with lung forced expiratory volume (47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells isolated from diseased lungs also exhibit altered versican production. For example, bronchial fibroblasts cultured from human asthma patients exhibited elevated versican production (20,21). Furthermore, in a study of induced sputum from patients with severe asthma, we found elevated levels of versican and HA over a 16-week period, which inversely correlated with lung forced expiratory volume (47).…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of a versican-enriched ECM coincides with invasion and retention of leukocytes within different compartments of the lung during these early inflammatory responses. Previous studies have shown that bronchial fibroblasts cultured from subjects with asthma have elevated production of versican (14,20,21), and in a recent study in a cockroach antigen-induced mouse model of asthma, we showed that versican, produced by airway epithelial cells, consistently accumulates in the subepithelial space and precedes infiltration of leukocytes, suggesting a specific immu-nomodulatory role for versican (22). Whether the acute lung inflammation stimulated by viral infection worsens asthma by altering the ECM microenvironment to facilitate leukocyte infiltration and accumulation is not yet known.…”
mentioning
confidence: 99%
“…BAL fluid containing 100 g protein was desalted by ultramembrane filtration and loaded using a pI 4 -7 immobilized pH gradient strip. We performed quantitative analysis with the image software PDQuest™ version 6.0 (Bio-Rad) (16,17 ).…”
Section: -D Gel Electrophoresismentioning
confidence: 99%
“…The second dimension was carried out at 100 V for 18 h until the tracking dye reached the end of the gels. The silver staining procedure was a modified protocol from Shevchenko et al and has previously been described (12,23).…”
Section: Protein Expression Analysismentioning
confidence: 70%
“…The ECM has an important role in influencing cell behavior through several different pathways and has recently been shown to be heterogeneously expressed in the lung of asthmatic patients (11,12). Components of the ECM such as HS-proteoglycans are considered to affect wound closure, re-epithelialization, and granulation tissue formation by storage and activation of cytokines and growth factors (13).…”
Section: Introductionmentioning
confidence: 99%